Incarnation Christology Offers Universal Salvation and Cultural Liberation for Catholics Torajan in South Sulawesi - Antonius Galih Arga Wiwin Aryanto; Cornelius Satrio Tonapa (Fakultas Teologi, Universitas Sanata Dharma, 2025)
The people of Toraja, South Sulawesi are known to have social stratification as part of their culture. Such stratification at the same time influenced the concept of salvation in their ancestral belief, Aluk To Dolo. Eternal salvation, in the concept of man's union with the highest God, Puang Matua, could only be obtained by those who have a high social class, Tana’ Bulaan. Meanwhile, those who came from low social classes, in addition to having limited space in society, also culturally-religiously were difficult to obtain salvation. Using the literature method, this paper aims to provide a christological solution to this religio-cultural problem, especially after Christianity encountered Toraja culture. As a result, contextual christology provided an answer to this gap. The Son as the ‘Word made flesh’ brought salvation to the Torajan people in general with no more social stratification boundaries in the new understanding.